O medo da morte como dispositivo de segurança que atua sobre a vida e a normalização dos sujeitos - Fernandes, Jaquelinne Alves (2018)
The study that we propose is based on the Analysis of the Speech of French line, from a theoretical perspective of Michel Foucault. Our purpose was to verify how fear of death acts as a security device, today, in the security society, for the purpose of controlling and preserving life. Thinking about this, we assume that, according to Foucault (2008), it is only possible to live in society through power relations, which are certified by devices, among them the security device. We believe that fear of death was produced by the security society, constituting itself as a mechanism of power, that acts in society, acting on the subjects, and can be taken as a device. This way, the fear of death is a device in the security society and, in order for it to function properly and achieve the desired purpose, the preservation of life, it is necessary for society to be normalized. Therefore, fear of death is a security device that acts in the security society, regulated by norms, with the purpose of regulating life, through biopower. In the modern state, it is a social norm to use mechanisms and technologies that work to preserve life and reduce risks; and norms are responsible, also, for the objectification and subjectivation of the subjects. Thus, the constitution of the normal subject (that follows the norms) and of the abnormal subject (the one that does not follow the norms) occurs according to the norms, among them the one that determines that the life must be preserved. For our study, we chose as analysis corpus the films Apocalypse Now and Falling Down; and the sixth season of The Walking Dead to evidence the fear of death acting as a security device and its relation to the norm. Trough our analyzes we could establish that the subjects of the corpora are constituted as abnormal because they do not subjectivize themselves by the norm that determines that life should be preserved, nor do they constitute the functioning of the fear of death as a security device.